Interrupting Sitting Time with Regular Walks Attenuates Postprandial Triglycerides - Miyashita, M.; Edamoto, K.; Kidokoro, T.; Yanaoka, T.; Kashiwabara, K.; Takahashi, M.; Burns, S. (International Journal of Sports Medicine, 2016)
We compared the effects of prolonged sitting with the effects of sitting interrupted by regular walking and the effects of prolonged sitting after continuous walking on postprandial triglyceride in postmenopausal women. 15 participants completed 3 trials in random order: 1) prolonged sitting, 2) regular walking, and 3) prolonged sitting preceded by continuous walking. During the sitting trial, participants rested for 8 h. For the walking trials, participants walked briskly in either twenty 90-sec bouts over 8 h or one 30-min bout in the morning (09:00–09:30). Except for walking, both exercise trials mimicked the sitting trial. In each trial, participants consumed a breakfast (08:00) and lunch (11:00). Blood samples were collected in the fasted state and at 2, 4, 6 and 8 h after breakfast. The serum triglyceride incremental area under the curve was 15 and 14% lower after regular walking compared with prolonged sitting and prolonged sitting after continuous walking (4.73±2.50 vs. 5.52±2.95 vs. 5.50±2.59 mmol/L∙8 h respectively, main effect of trial: P=0.023). Regularly interrupting sitting time with brief bouts of physical activity can reduce postprandial triglyceride in postmenopausal women.
Keywords: postprandial period; sedentary lifestyle; short bouts of walking